Participation Report at the Biennial Africa Climate-Smart Agriculture Conference (FARA) in Ghana - Osumba, Joab J.L. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Many attempts have been made at the global level to tackle the issues of climate adaptation and resilience of food systems and agriculture. Attention has been focused on the concept and practice of climate-smart agriculture (CSA), which seems to be well established as a keyword in agricultural development. The Forum for Agricultural Research in Africa (FARA) and other organizations that are coordinating agricultural research in Africa are channeling attention to the issues of CSA, through scoping studies and mapping of various CSA initiatives to identify the state of knowledge, available technologies, and institutional arrangement to advance African agricultural development. Since 2020 FARA and partners organise a biennial CSA conference as a forum for discussion among the different stakeholders involved in the generation and use of climate-relevant agricultural knowledge, technologies, and innovations in Africa. The conference forms a major platform for stock-taking, reporting on initiatives, and joint identification and prioritization of the next line of action, especially in technology generation and use. The conference also engages in policy and advocacy discussions, and includes presentations of research papers, to nurture the policy and technical dialogue among academicians, researchers, managers, policymakers, small producer organizations, civil society organizations, agribusiness sector, and students.